How to Apply Authentic Assessment in Indonesian Language Learning - Erwin Harianto (Didaktika: Jurnal Kependidikan, 2021)
Educational reform is important to do in achieving the objectives of learning Indonesian in schools, through re-designing. it's time for a teacher to carry out the learning, teaching, and assessment process by changing the conventional form of assessment that is only results-oriented into a form of authentic assessment. Authentic assessment is an assessment that has many advantages, including: meeting the validity requirements of an assessment, accommodating student diversity, meeting competency achievement standards, and being oriented to student learning processes and outcomes that cover all aspects, from cognitive, affective, to psychomotor aspects. Authentic assessment includes a variety of assessment methods that allow students to demonstrate their ability to complete assignments and find solutions. Thus, student motivation will be awakened and students will enjoy learning.